2021
DOI: 10.2147/opth.s311070
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled, Prospective Study of the Effectiveness and Safety of an Intracanalicular Dexamethasone Ophthalmic Insert (0.4 Mg) for the Treatment of Post-Operative Inflammation in Patients Undergoing Refractive Lens Exchange (RLE)

Abstract: Purpose: To determine patient preference and treatment outcomes with an intracanalicular dexamethasone (0.4 mg) insert compared to standard steroid drop regimen in the contralateral eye following bilateral RLE surgery. Methods: This is a prospective, open-label, interventional, randomized, controlled study in 20 subjects who underwent bilateral RLE. Each patient served as their own control with one eye randomized to the intracanalicular insert (Group A) placed at the time of surgery and the contralateral rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“… 19 , 20 , 22 In addition to cataract patients, physicians most often indicated that on-label use of DEX could benefit patients undergoing pterygium surgery, corneal surgery, and refractive procedures (which have been studied in LASIK and refractive lens exchange) ( Table 2 ). 23 , 24 One of the greatest perceived values of DEX according to physicians was its ability to treat the ocular surface with a preservative-free formulation. As might be expected based on the high prevalence of dry eye in the United States, 25 , 26 dry eye was the most common comorbidity of the cataract surgery patients in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 19 , 20 , 22 In addition to cataract patients, physicians most often indicated that on-label use of DEX could benefit patients undergoing pterygium surgery, corneal surgery, and refractive procedures (which have been studied in LASIK and refractive lens exchange) ( Table 2 ). 23 , 24 One of the greatest perceived values of DEX according to physicians was its ability to treat the ocular surface with a preservative-free formulation. As might be expected based on the high prevalence of dry eye in the United States, 25 , 26 dry eye was the most common comorbidity of the cataract surgery patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 2–4 , 12 They may improve clinic efficiency by decreasing the need for filling a prescription, which is time-efficient for both healthcare providers as well as patients. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11–13 It is approved in the United States for the control of pain and inflammation following ocular surgery, 14 and its role in postoperative care has been demonstrated following cataract extraction in adults 11 , 12 , 46–48 and children, 49 pars plana vitrectomy, 20 as well as refractive surgical procedures. 18 , 19 , 50 Phase 2 and 3 trials have also evaluated DEX for chronic inflammation associated with allergic conjunctivitis and reported short-term improvements in itching and conjunctival hyperemia. 51–53 Given the role of inflammation in MGD, we hypothesized in this study that DEX may provide additional therapeutic benefit when combined with thermal pulsation therapy for MGD.…”
Section: Discussionmentioning
confidence: 99%
“…No formal power analysis was conducted, and the sample size was set at 40 eyes based on the sample size used in several similar prior studies. [18][19][20] Chi-square tests were used to compare proportions and t-tests to compare means. The level of significance was set at 0.05.…”
Section: Methodsmentioning
confidence: 99%